Early AbobotulinumtoxinA (Dysport®) in Post-Stroke Adult Upper Limb Spasticity: ONTIME Pilot Study - Raymond L Rosales; Jovita Balcaitiene; Hugues Berard; Pascal Maisonobe; Khean Jin Goh; Witsanu Kumthornthip; Mazlina Mazlan; Lydia Abdul Latif; Mary Mildred D. Delos Santos; Chayaporn Chotiyarnwong; Phakamas Tanvijit; Odessa Nuez; et al. (Toxins, 2018)
The ONTIME study investigated whether early post-stroke abobotulinumtoxinA injection delays appearance or progression of upper limb spasticity (ULS) symptoms. ONTIME (NCT02321436) was a 28-week, exploratory, double-blind, randomized, placebo-controlled study of abobotulinumtoxinA 500U in patients with ULS (Modified Ashworth Scale [MAS] score ≥ 2) 2–12 weeks post-stroke. Patients were either symptomatic or asymptomatic (only increased MAS) at baseline. Primary efficacy outcome measure: time between injection and visit at which re-injection criteria were met (MAS ≥ 2 and ≥1, sign of symptomatic spasticity: pain, involuntary movements, impaired active or passive function). Forty-two patients were randomized (abobotulinumtoxinA 500U: n = 28; placebo: n = 14) with median 5.86 weeks since stroke. Median time to reach re-injection criteria was significantly longer for abobotulinumtoxinA (156 days) than placebo (32 days; log-rank: p = 0.0176; Wilcoxon: p = 0.0480). Eleven (39.3%) patients receiving abobotulinumtoxinA did not require re-injection for ≥28 weeks versus two (14.3%) in placebo group. In this exploratory study, early abobotulinumtoxinA treatment significantly delayed time to reach re-injection criteria compared with placebo in patients with post-stroke ULS. These findings suggest an optimal time for post-stroke spasticity management and help determine the design and sample sizes for larger confirmatory studies.